Microvascular impairments detected by optical coherence tomography angiography in multiple sclerosis patients: A systematic review and meta-analysis - Liu, Jing; Song, Shuang; Gu, Xiaoya; Li, Hui; Yu, Xiaobing (Frontiers in Neuroscience, 2023)
Purpose: A systematic review and meta-analysis was conducted to investigate changes in retinal and choroidal microvasculature in patients with multiple sclerosis (MS) using optical coherence tomography angiography (OCTA). Methods: PubMed and Google Scholar were searched for studies that compared retinal and choroidal microvasculature between MS and healthy controls (HC) with OCTA. MS patients were divided into 2 groups: MS with (MSON) or without optic neuritis (MSNON). Results: Totally, 13 studies including 996 MS eyes and 847 HC eyes were included. Compared with the HC, the vessel density of the whole superficial vascular complex (SVC) was reduced by 2.27% and 4.30% in the MSNON and MSON groups, respectively. The peripapillary vessel density was 2.28% lower and 4.96% lower in the MSNON and MSON groups, respectively, than in the HC. Furthermore, the MSON group had significant lower vessel density of the SVC (mean difference [MD] =-2.17%, P<0.01) and lower peripapillary vessel density (MD=-2.02%, P=0.02) than the MSNON group. No significant difference was found in the deep vascular complex or choriocapillaris densities among MSNON, MSON or HC groups (P>0.05). Meta-regression analyses suggested that illness duration and the Expanded Disability Status Scale scores of MS patients were possible sources of heterogeneity (P<0.05). Conclusion: The retinal SVC and peripapillary vessel density decreased significantly in MS eyes, especially in eyes with optic neuritis. Retinal microvasculature is a potential biomarker of disease progression in MS.